Nonlinear Vibration of Saturated Porous Functionally Graded Plate in Thermal Environment - Quan, Tran Quoc; Hung, Nguyen Dang; Thang, Vu Duc (VNU Journal of Science: Mathematics - Physics; Vol 40 No 1DO - 10.25073/2588-1124/vnumap.4884, 2024)
In this work we studied investigates the nonlinear vibrations of a rectangular saturated porous functionally graded (FG) plate on elastic foundations in thermal environment. The mechanical properties of the saturated porous material vary smoothly with the thickness in three different distributions of porosity including uniform, symmetrically irregular, and asymmetrically irregular. The basic equations are employed by the Reddy’s higher order shear deformation theory, incorporating the geometrically nonlinear von Kármán strain-displacement relationship, stress-strain relations based on the elastic theory for porous materials by Biot, and an analytical solution obtained through the Galerkin method and Airy’s stress function for the simply supported plate. The influence of the geometrical and material parameters, elastic foundations and temperature increment on the nonlinear vibrations of the saturated porous FG plate were specifically evaluated through numerical investigations.